A retrospective evaluation of a score system adopted by the Ministry of Health, Brazil in the diagnosis of pulmonary tuberculosis in childhood: a case control study - Clemax Couto Sant'Anna; Cláudia T. S. Orfaliais; Maria de Fátima B. Pombo March (Revista do Instituto de Medicina Tropical de São Paulo, 2003)
Based on a retrospective case-control study we evaluated the score system adopted by the Ministry of Health of Brazil (Ministério da Saúde - MS), to diagnose pulmonary tuberculosis (PTB) in childhood. This system is independent of bacteriological or histopathological data to define a very likely (> or = 40 points), possible (30-35 points) or unlikely (< or = 25 points) diagnosis of tuberculosis. Records of hospitalized non-infected HIV children at the Instituto de Puericultura e Pediatria Martagão Gesteira of Federal University of Rio de Janeiro (IPPMG-UFRJ), were reviewed. Patients were adjusted for age and divided in two different groups: 45 subjects in the case group (culture-positive) [mean of age = 10.64 mo; SD 9.66]; and 96 in the control group (culture-negative and clinic criteria that dismissed the disease) [mean of age = 11.79 mo.; SD 11.31]. Among the variables analyzed, the radiological status had the greater impact into the diagnosis (OR = 25.39), followed by exposure to adult with tuberculosis (OR = 10.67), tuberculin skin test >10mm (OR = 8.23). The best cut-off point to the diagnosis of PTB was 30 points, where the score system was more accurate, with sensitivity of 88.9% and specificity of 86.5%.